The Influence of Company Activities, Growth, and Independent Commissioners on Sustainability Reports With the Type of Industry as a Moderating Variable - Niswah Baroroh; Indah Anisykurlillah; Heri Yanto; Fajri Kusumaningrum (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2022)
Objective: This research aims to analyze the influence of inventory turnover, asset growth, and independent commissioners’ meeting frequency on the sustainability report with industry type (nonfinancial industry) as the moderating variable.Methods: The research population is 44 non-financial companies listed on the Indonesia Stock Exchange and published their sustainability reports from 2018 to 2020. The sample is taken using a purposive sampling technique with 38 companies and 114 units of analysis. Hypothesis testing is done by using regression analysis by conducting the moderated regression analysis (MRA).Findings: The results show that the inventory turnover positively influence the disclosure of the sustainability report. Asset Growth negatively affects the disclosure of the sustainability report. Meanwhile, the independent commissioner’s meeting frequency does not affect the disclosure of the sustainability report. Next, the type of industry strengthens the relationship between the independent commissioners’ meeting frequency on the disclosure of the sustainability report. The type of industry weakens the relationship between the inventory turnover on the disclosure of the sustainability report. The type of industry cannot moderate the relationship between the influence of asset growth and the disclosure of the sustainability report.Originality: This research originality is the use of industry type as a moderating variable to strengthen the influence of inventory turnover, asset growth, and independent commissioners’ meeting frequency on the disclosure of the sustainability report